2010
DOI: 10.1007/s10201-010-0336-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus and temperature on chlorophyll a contents and cell sizes of Scenedesmus obliquus and Microcystis aeruginosa

Abstract: An experiment was carried out to evaluate the effects of phosphorus concentration (1, 4 and 10 mg l -1 ) and temperature (15 and 25°C) on chlorophyll a (chl a) contents and cell size/volume of green alga Scenedesmus obliquus and blue green alga Microcystis aeruginosa. Long-term field data from Lake Taihu, a large, shallow eutrophic lake between Jiangsu and Zhejiang Provinces, China, was also used to evaluate the effect of temperature on the model between chl a and total phosphorus (TP). The chl a content of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 31 publications
4
37
0
Order By: Relevance
“…Similarly, chlorophyll and carotenoid contents were lower in the green algae Chlamydomonas reinhardtii grown under 15 • C compared to 25 • C . Chen et al (2010), in turns, observed an increased chlorophyll content in the cyanobacteria Microcystis aeruginosa grown at 25 • C in relation to 10 • C. On the other hand, chlorophyll content was not significantly affected by temperature in the diatom Navicula pelliculosa (at 10, 15, and 25 • C) (Chalifour and Juneau, 2011) or in the cyanobacteria Merismopedia tenuissima and Oscillatoria sp. (at 15, 20, 25, and 30 • C) (Coles and Jones, 2000).…”
Section: Thermal-acclimationmentioning
confidence: 87%
“…Similarly, chlorophyll and carotenoid contents were lower in the green algae Chlamydomonas reinhardtii grown under 15 • C compared to 25 • C . Chen et al (2010), in turns, observed an increased chlorophyll content in the cyanobacteria Microcystis aeruginosa grown at 25 • C in relation to 10 • C. On the other hand, chlorophyll content was not significantly affected by temperature in the diatom Navicula pelliculosa (at 10, 15, and 25 • C) (Chalifour and Juneau, 2011) or in the cyanobacteria Merismopedia tenuissima and Oscillatoria sp. (at 15, 20, 25, and 30 • C) (Coles and Jones, 2000).…”
Section: Thermal-acclimationmentioning
confidence: 87%
“…The average cell biovolume of S. obliquus used in the current study was determined as 102 μm 3 cell −1 via a laser particle analyzer (Li et al 2015a) which was slightly lower than 121 μm 3 cell −1 as reported by Lürling (2006). The average cell biovolume of M. aeruginosa (FACHB 469) was calculated as 11.5 μm 3 cell −1 according our previous study (Li et al 2013b), which was much lower than 16 μm 3 cell −1 reported by Chen et al (2011b) (setting its diameter as 3.1 μm and calculated as a sphere). The maximum cell density of S .…”
Section: Discussionmentioning
confidence: 98%
“…The influence of genetic factors on chlorophyll content was confirmed by Bojovic and Markovic (2009) who investigated the variability of the chlorophyll content of wheat leaf with cultivar. Furthermore, chlorophyll content is usually affected by various environmental factors such as temperature, photoperiod, nitrogen, water and degree of maturity (Chen et al, 2011;Lee et al, 2011).…”
Section: Total Chlorophyll Chlorophyll a And Chlorophyll Bmentioning
confidence: 99%